Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Pertanahan di Lingkungan Kantor Wilayah Badan Pertanahan Nasional Provinsi Jawa Barat - Biller Panjaitan (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
The objectives of this research are: 1) to reveal descriptions of work motivation and employee’s performance of the Regional West Java Land Office, 2) to test hypothesis of the relationships and influences among work motivation and employee’s performance.The type of this research are descriptive and verificative research. The method used of this research is survey method.Sample size are 219 employees of the Regional West Java Land Office who are sampled by proportional stratified random sampling method. The data used in this research were primary data collected by questioners. The analysis method used in this research are descriptive and hypothesis testing analysis with the analysis tool using the structural equation modeling ( SEM ) and processed by LISREL 8.51 ( Linier Structural Relationship ) programme 8.51 for windows software. The results of descriptive analysis indicate that the work motivation and employee’s performance were categorized ‘good’, however work motivation still needs to be improved. Based on the results of hypothesis testing indicate that there was positive and significant relationship between the independent variables It means have positive sinergy with work motivation to increase employee’s performance in the Regional West Java Land Office. Based on descriptive and verificative analysis, it is necessary to recommend that decision makers of the Regional West Java Land Office have to determine policies on developing human resources,on the work motivation therefore in turn it will effect on employee’s performance improvement.